K/AR DATING OF BUKIT ASAM AND BUKIT KENDI INTRUSIONS RELATED TO AGE OF MATURITY AND INCREASING OF COAL QUALITY IN TANJUNG ENIM AREA, SOUTH-SUMATERA - HARRY UTOYO UTOYO (Puslitbang tekMIRA, 2007)
Coal bearing Muara Enim Formation is widely spread in Muara Enim, especially in Tanjung Enim District, South-Sumatera Province. Field observations display increasing maturity and quality towards Bukit Asam and Bukit Kendi intrusions. Potassium argons age analysis revealed that Bukit Asam is 0,9203 ± 0,26 million years in age and Bukit Kendi is 1,1472 ± 0,29 million years in age respectively, while Bukit Serilo displays negative age. These K/Ar ages result revealed that increasing maturity and quality of coal of the Bukit Asam and Bukit Kendi have taken place since 1,14 million years.